Increased anxiety of mice lacking the serotonin(1A) receptor - Parks, Christopher L. (The National Academy of Sciences, 1998)
Brain serotonin (5-HT) has been implicated in a number of physiological processes and pathological conditions. These effects are mediated by at least 14 different 5-HT receptors. We have inactivated the gene encoding the 5-HT(1A) receptor in mice and found that receptor-deficient animals have an increased tendency to avoid a novel and fearful environment and to escape a stressful situation, behaviors consistent with an increased anxiety and stress response. Based on the role of the 5-HT(1A) receptor in the feedback regulation of the 5-HT system, we hypothesize that an increased serotonergic neurotransmission is responsible for the anxiety-like behavior of receptor-deficient animals. This view is consistent with earlier studies showing that pharmacological activation of the 5-HT system is anxiogenic in animal models and also in humans.